Reconstituição de pedra atérmica com uso de resíduo da extração de quartzito para aplicação como revestimento de fachada em edifícios - Queiroz, Clarissa de Andrade (2017)
Quartzite is an ornamental rock used to produce coatings applied on residential façades, gardens, pavement of patios, sidewalks, saunas and swimming pools. It is a porous rock, has low water absorption and is also known as "cold stone". When used as an external coating on façades, it can contribute to the reduction of the heat flow to the internal environments, since when receiving the solar radiation, it has low propagation of the heat waves, which is important in the context of the tropical climate. Despite the improvement in the thermal behavior of the vertical element that can be added to the building with the use of the quartzite, there is an environmental issue related to the impact of rock extraction due to the large generation of waste. In this article, a study is presented that aims to develop a pre-molded that compatibilizes the use of the residue of quartzite extraction with an application also as facade cladding in buildings and that takes advantage of the thermal characteristic of the original material, so as to create a barrier to the flow of heat into the building. Thus, while there is a possibility of reducing impacts on the natural environment, a positive contribution to the built environment can be made. The method used for the present study was that of reconstituted stones, through the preforming of small pieces using a composite, with residues of quartzite stone powder and vegetable polyurethane resin obtained from castor oil. The results confirmed that it is possible to cast reconstituted stones with higher thermal capacity, which is interesting for facade cladding in buildings located in tropical climate. The proposed stone, in addition to meeting the mechanical physical requirements for facade cladding, has lower conductivity and thermal transmittance compared to quartzite.